Zr(HSO4)4: An Efficient Catalyst for the Synthesis of 3-(2'- Benzothiazolyl)-2,3-dihydroquinazolin- 4(1H)-ones - Liqiang Wu (E-Journal of Chemistry)
A simple and efficient synthesis of 3-(2'-benzothiazolyl)-2,3-dihydro quinazolin-4(1H)- ones has been accomplished by the one-pot condensation of isatoic anhydride, aldehyde and 2-aminobenzothiazole under solvent-free conditions in the presence of Zr(HSO4)4.